Quantum AI-Enhanced Nanomagnetic Sensors for Biomedical Imaging - Biswas, Debarghya; Balkrishna, Sutar Manisha; Aggarwal, Rashi (International Journal of Engineering, Science and Information Technology, 2025)
An extremely high impact advance in biomedical imaging is quantum AI-enhanced nanomagnetic sensors, where the combination of quantum coherence and nano automotive AI provides ? substantial increase in medical diagnosis precision. This research outlines the QAI-NMS System that utilises quantum dots and nitrogen vacancy (NV) centres in diamond to improve the bio-magnetic sensing capability to sub-picoTesla sensitivity. The AI-driven quantum noise suppression and Quantum Classical Computing are hybrid, and both augment the signal clarity and reduce the quantum decoherence of the signal. The system uses real-time signal optimisation based on deep reinforcement learning, as well as high-fidelity biomedical imaging by the variational quantum algorithms. The conventional methods like MRI and CT are much invasive, radiated, and portable imaging techniques with less sensitivity, but QAI NMS is non-invasive, radiation-free, and portable imaging with higher sensitivity. Other can be developed, such as early cancer detection, neural activity mapping of the brain for a brain computer interface, non-invasive cardiac monitoring, and even to track drug delivery to a given area without actually interfering with the body. A quantitative analysis is provided for signal-to-noise ratio, quantum-assisted resolution enhancement, as well as computational efficiency, and experimental evaluations are presented that exhibit significantly improved signal-to-noise ratio. This study constitutes a paradigm shift in biomedical imaging by merging quantum technologies with AI analytics for realising real-time high-resolution noise-immune imaging. The proposed framework here would have a great application in the next generation of diagnostic tools, offering unparalleled precision in health monitoring as well as medical imaging. The future research will miniaturise, deploy, and augment what appeared quantum in nature to provide the capability for real-time clinical deployment.